2012
DOI: 10.1038/nn.3037
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine/juxtaparacrine regulation of axon fasciculation by Slit-Robo signaling

Abstract: Axons travel to their targets in bundles or fascicles, but the molecules regulating fasciculation remain incompletely characterized. We found that Slit2 and its Robo receptors are expressed by motor axons, and that inactivation of Slit2 or Robo1 and Robo2 in mice caused axons to defasciculate prematurely at muscle targets. In vitro, Slit2 secreted by motoneurons regulated fasciculation through Robo1 and Robo2. These results support the idea that Slit2 promotes axon fasciculation via an autocrine and/or juxtapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 14 publications
3
85
0
Order By: Relevance
“…Mammalian motoneurons differ from commissural neurons in that they co-express Robo1/2, Dcc and Slit2. In this context, Slit2 seems to have an autocrine function that controls motor axon fasciculation towards their muscle targets (Jaworski and Tessier-Lavigne, 2012). Within the spinal cord, Slit binding to Robo1/2 on motor axons silences Dcc function and prevents these axons from being attracted by netrin 1 at the floor plate (Bai et al, 2011).…”
Section: Slit-robo Signaling At the Spinal Cord Midlinementioning
confidence: 99%
“…Mammalian motoneurons differ from commissural neurons in that they co-express Robo1/2, Dcc and Slit2. In this context, Slit2 seems to have an autocrine function that controls motor axon fasciculation towards their muscle targets (Jaworski and Tessier-Lavigne, 2012). Within the spinal cord, Slit binding to Robo1/2 on motor axons silences Dcc function and prevents these axons from being attracted by netrin 1 at the floor plate (Bai et al, 2011).…”
Section: Slit-robo Signaling At the Spinal Cord Midlinementioning
confidence: 99%
“…In our study, the increase of the NgR1-immunohistochemical signal in the highly Nogo-A-positive RGCs of Cnp-Cre þ / À xRtn4 flox/flox KOs could reflect cisinteractions between the ligand and receptor. At the cell membrane, the sequestration and inactivation of ligands by cis-binding to adjacent receptors has previously been described to prevent trans-activation in the case of guidance molecules such as Ephrins, 16 semaphorins 17 or Slit-Robo, 56 but also for the Notch signaling pathway. 57 The co-expression of Nogo-A and NgR1 in RGCs of Cnp-Cre þ / À xRtn4 flox/flox KO mice could prevent downstream activation of Rho-A after ONC and Nogo-A overexpression in F11 cells could partially counteract neurite outgrowth inhibition induced by Nogo-A-D20.…”
Section: Moreover Inflammation-inducing Agents Such As Zymosan or Pamentioning
confidence: 99%
“…Slit2 and Robo1 are expressed in phrenic motor neurons and myoblasts forming costal muscles, respectively, during diaphragm development Recent findings have revealed that Sli-Robo signaling does not only have a direct effect on phrenic nerve fasciculation (Jaworski and Tessier-Lavigne, 2012), but that Slit proteins, released by the sclerotome, can also repel pioneering myoblasts during early development of avian embryos (Halperin-Barlev and Kalcheim, 2011). At later stages, migrating pioneering myoblasts are attracted by Slit proteins released by the tendon to guide them to their final destination in Drosophila (Kramer, 2001).…”
Section: Misprojecting Phrenic Axons Innervate Ectopic Muscles In Thementioning
confidence: 99%
“…Nevertheless, it is unlikely that axon-derived Slit1 has a major role in vivo, as it is not expressed in phrenic motor neurons during the innervation of the diaphragm (Jaworski and Tessier-Lavigne, 2012).…”
Section: Diaphragm Myoblasts From Costal Muscles Are Attracted By Slitsmentioning
confidence: 99%
See 1 more Smart Citation